2021
DOI: 10.1029/2020av000321
|View full text |Cite
|
Sign up to set email alerts
|

Drainage Canals in Southeast Asian Peatlands Increase Carbon Emissions

Abstract: In these wetland environments, persistent flooding and anoxic conditions suppress decomposition rates, allowing organic material to accumulate over time in deep peat deposits. This process, compounded over millennia, has made Southeast Asian (SEA) peatlands one of the world's largest terrestrial pools of organic carbon: an estimated 67 Gt of carbon are stored in peatlands in Indonesia, Malaysia, and Brunei (Page et al., 2011; Warren et al., 2017). In recent decades, this carbon sink has been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…Although the degree of artificial drainage varies spatially and in time, we approximated the effects of drainage using a single set of representative parameters, similar to how vegetation with different surface energy exchange characteristics is combined in a single LSM land cover type. The discharge function of PEATCLSM Trop,Drain (see Section 2.2.4 , and Figure 6b ) was developed using information on drainage canals in Southeast Asian peatlands (Dadap et al., 2021 ). This map of drainage canals could be used to develop a spatially varying discharge function for PEATCLSM Trop,Drain , but also to spatially distinguish between natural and drained peatlands using a threshold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the degree of artificial drainage varies spatially and in time, we approximated the effects of drainage using a single set of representative parameters, similar to how vegetation with different surface energy exchange characteristics is combined in a single LSM land cover type. The discharge function of PEATCLSM Trop,Drain (see Section 2.2.4 , and Figure 6b ) was developed using information on drainage canals in Southeast Asian peatlands (Dadap et al., 2021 ). This map of drainage canals could be used to develop a spatially varying discharge function for PEATCLSM Trop,Drain , but also to spatially distinguish between natural and drained peatlands using a threshold.…”
Section: Discussionmentioning
confidence: 99%
“…However, the map only represents current drainage canals and doesn't take local canal management into account. Although land use has been mapped over time (Miettinen et al., 2016 ), drainage is not always well‐coordinated with it (Dadap et al., 2021 ), making the drainage map's usefulness for long simulation periods uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with the latest measurements of surface water extent from NISAR (also to launch in 2022), and height measurements from modern laser and radar altimeters (e.g., ICESat-2, Sentinel 6 Michael Freilich), the availability of data for surface water studies is rapidly expanding, leading to major breakthroughs (Cooley et al, 2021). The influx of commercial imagery from companies such as Maxar and Planet is also changing this field rapidly by enabling frequent (∼daily), fine spatial (≤3 m) observations of surface water extent (Cooley et al, 2017(Cooley et al, , 2019Dadap et al, 2021), especially in smaller lakes and rivers. The combination of the first dedicated surface water mission (SWOT), widely available fine-resolution optical (SmallSats, Sentinel-2), and radar (NISAR) imagery, and additional spaceborne altimeters (Sentinel 6 Michael Freilich, ICESat-2) mean that a "golden age" of surface water remote sensing is clearly on the horizon.…”
Section: Progress In Hydrologic Remote Sensingmentioning
confidence: 99%
“…Being utilized extensively for the agricultural sector, such as oil palm plantation with an alarming rate, the uprising risk of C emission in peatland has raised global concern (Wijedasa et al, 2017;Leifeld et al, 2019;Dadap et al, 2021). Recent reports revealed that a large peatland area in the Riau region had been cultivated by oil palm plantations (Ramdani and Hino 2013;Adrianto et al, 2020), ranked Riau as the largest holder and producer of oil palm plantation over the country (BPS, 2021).…”
Section: Introductionmentioning
confidence: 99%